Natural product‐based nanomedicine applied to fungal infection treatment: A review of the last 4 years. (29th May 2022) - Marena, Gabriel Davi; Ramos, Matheus Aparecido dos Santos; Carvalho, Gabriela Corrêa; Junior, José Alberto Paris; Resende, Flávia Aparecida; Corrêa, Ione; Ono, Gabriela Yuki Bressanim; Sousa Araujo, Victor Hugo; de Camargo, Bruna Almeida Furquim; Bauab, Tais Maria; Chorilli, Marlus
Abstract: Fungal infections are one of the main public health problems, especially in immunocompromised patients, nosocomial environments, patients with chronic diseases, and transplant recipients. These diseases are increasingly frequent and lethal because the microorganism has a high capacity to acquire resistance to available therapy. The main resistance factors are the emergence of new strains and the uncontrolled use of antifungals. It is, therefore, important to develop new methods that contribute to combating fungal diseases in the clinical area. Natural products have considerable potential for the development of new drugs with antifungal activity, mainly due to their biocompatibility and low toxic effect. This promising antimicrobial activity of natural products is mainly due to the presence of flavonoids, terpenes, and quinones, which explains their antifungal potential. Pharmaceutical nanotechnology has been explored to enhance the delivery, selectivity, and clinical efficacy of these products. Nanotechnological systems provide a safe and selective environment for various substances, such as natural products, improving antifungal activity. However, further safety experiments (in vivo or clinical trials) need to be carried out to prove the therapeutic action of natural products, since they may have undesirable, toxic, and mutagenic effects. Therefore, this review article addresses the main nanotechnological methods using natural products for effective future treatment against the main fungal diseases.